Critique session in art & design studio: a framework for art education / Zuhaili Akmal Ismail - Ismail, Zuhaili Akmal (2017)
Critique session for art students is for good ideas to emerge while simultaneously refining the feedback necessary to resolve any problems within the students’ design work. Unfortunately, students and art educators perceived this session as a daunting process due to the non-existent strategies or frameworks in creating a positive and collaborative learning approach for both parties. Moreover, for art educators in Malaysia, there are no references for the general guideline to good practices in critique session in the documents provided by the Malaysia Qualifications Agency (MQA) Code of Practice for Programme Accreditation (COPPA) and the Code of Practice for Institutional Audit (COPIA). This research is a mixed methods research which utilized both qualitative and quantitative methods that identify factors that contribute to student satisfaction and dissatisfaction in the existing critique session, design and develop a critique session framework for the teaching and learning in art & design studio and evaluate the effectiveness of the new framework for the teaching and learning in art & design studio. The research method framework is divided into three phases: the pilot study (online survey), pre-design and development (observation & focus group) and post-design and development (online survey). The pilot study (online survey) suggested a low rate of students’ satisfaction towards the existing critique session students’ and general dispositions toward five dissatisfaction factors including course activity, processed induced, educator’s performance, teaching materials and didactic competencies. Through the pre-design and development (observation), the researcher discovered that there are two types of student behaviours and learning preferences which are non-participants and semi-active participants. These learning preferences were later adapted in designing a new framework, the ZA Framework. Through the online survey in the post-design and development phase, the total mean score for all dimensions (positive climate, class management, productivity, student engagement and teacher sensitivity) were almost to 3 (high agreement), reflecting a positive student attitude towards the ZA Framework. The majority of each dimension was under dispersed which fulfill the model fit. This finding is in agreement that the ZA Framework allows the expression and elaboration of instrumental meanings within the Malaysia art & design studio through a critique session.